A randomized, controlled proof-of-concept trial evaluating durable effects of memory flexibility training (MemFlex) on autobiographical memory distortions and on relapse of recurrent major depressive disorder over 12 months. (May 2021) - Hitchcock, Caitlin; Smith, Alicia J.; Elliott, Rachel; O'Leary, Cliodhna; Gormley, Siobhan; Parker, Jenna; Patel, Shivam D.; Esteves, Carlos V.; Rodrigues, Evangeline; Hammond, Emily; Watson, Peter; Werner-Seidler, Aliza; et al.
Abstract: Low-intensity psychological interventions that target cognitive risk factors for depressive relapse may improve access to relapse prevention programs and thereby reduce subsequent risk. This study provides the first evaluation of an autobiographical memory-based intervention for relapse prevention, to establish whether memory-training programs that are efficacious for acute depression may also aid those currently in remission. We also provide the longest follow-up to-date of the effects of autobiographical memory training on autobiographical memory processes themselves. This pre-registered randomized-controlled proof-of-concept trial ( N = 74) compared an autobiographical Memory Flexibility (MemFlex) intervention to Psychoeducation about cognitive-behavioral mechanisms which maintain depression. Both interventions were primarily self-guided, and delivered via paper workbooks completed over four weeks. The key cognitive outcome was ability to retrieve and alternate between specific and general autobiographical memories. Co-primary clinical outcomes were time until depressive relapse and depression-free days in the twelve-months following intervention. Results indicated a small-moderate effect size ( d = 0.35) in favor of MemFlex for the cognitive outcome. A small Hazard Ratio (1.08) was observed for time until depressive relapse, along with a negligible effect size for depression-free days ( d = 0.11). Although MemFlex produced long-term improvement in memory retrieval skills, there was little support for MemFlex as a relapse prevention program for depression. Editor highlights: Study evaluates autobiographical memory-based intervention for relapse prevention. Intervention-driven gains in autobiographical memory were maintained one year later. MemFlex did not reduce risk of depressive relapse any more than Psychoeducation. Autobiographical memory interventions may be best utilised as treatment programs.